Sosialisasi dan Pendampingan Pembuatan Izin Usaha serta Penyuluhan Pemasaran Digital UMKM di Kelurahan Ngipik - Firdaus, Veronica Mechy Luklu’ul; Kusumasari, Indah Respati (Jurnal Bisnis Indonesia, 2024)
In facing competition, MSMEs often face challenges in maintaining and improving the quality of theirproducts. Currently, the central and regional governments offer a lot of assistance, assistance andtraining to business actors as a form of service to the community. Legality is one of the challenges forMSME players to improve the quality of their products. One of the important factors in improving thequality of MSME products is legality. Many MSMEs in Ngipik Subdistrict still do not have a BusinessIdentification Number (NIB) even though they will get many benefits if they have a BusinessIdentification Number (NIB). There are still many who do not know the importance of businesslegality and think that creating a Business Identification Number (NIB) is long and complicated. Thiscounseling aims to introduce and increase understanding of NIB making. Activities will be carried outin August-November 2023 for MSMEs in Ngipik Village, Gresik. The methods used are socialization,mentoring and counseling. Implementation of activities includes conveying theory and practice ofcreating business legality. After the activity, the level of understanding of the training participantsregarding OSS, NIB increased.Keywords: MSMEs; Business Actors; NIB; Socialization; Mentoring, Counseling